TRANSCRIPTOMIC ANALYSIS OF NASOPHARYNGEAL SWAB FROM ASYMPTOMATIC AND MILDLY SYMPTOMATIC COVID-19 PATIENTS TO IDENTIFY CANDIDATES OF DISEASE SEVERITY MARKER - Faridl, Miftahul
COVID-19 involves multiple clinical manifestations which include asymptomatic and symptomatic. Symptomatic patients can be categorized into asymptomatic infection, mild illness, moderate illness, severe illness, and critical. Each category is presumed to occupy different pathological processes depending on the viral and host factors. Therefore, characterization of viral properties and host's molecular markers due to SARS-CoV-2 infection is relevant to be investigated. This study aims to analyze viral variants and identify transcriptomic and coinfection profiles of asymptomatic and mildly symptomatic patients. Total RNA was extracted from nasopharyngeal swab samples of asymptomatic (n=2) and mildly symptomatic (n=2) patients. A cDNA library was synthesized using Illumina Stranded Total RNA Prep with Ribo-Zero™ Plus to obtain total RNA with rRNA depletion. Sequencing was performed in Illumina NextSeq 550 system, resulting in 100 bp long reads. SARS-CoV-2 genome assembly was carried out using the web-based program DRAGEN RNA Pathogen Detection (BaseSpace Illumina). Quality control analysis and reads assembly onto Homo sapiens genome (hg19 version) were performed using Geneious software (v.2021.1). Differentially expressed genes were analyzed using the R package DESeq2. After that, R package clusterProfiler was operated to study the enriched gene ontologies. Coinfections were identified using DRAGEN Metagenomics Pipeline (BaseSpace Illumina). This study shows that Pango Lineage variants of B.1.1 or B.1.1.398 infected both asymptomatic and symptomatic patients without affecting the clinical manifestations. Principal component and clustering analysis showed differences in the global expression of both groups of patients. The two groups were subjected to upper respiratory tract ciliated tissue structure modification and mRNA splicing deregulation which are SARS-CoV-2 infection strategies on host tissue. Individually, asymptomatic patients underwent modulation in their macroautophagy, epigenetics, and cell cycle processes. Meanwhile, mildly symptomatic patients underwent disruption in their nuclear transport system and RNA metabolism. Global gene expression occurs in both groups and is correlated with their level of severity. Downregulation of autophagy-related genes (ATG) in autophagy and inflammasome response, as well iv as interleukin-15 (IL15), can be suggested as important markers in asymptomatic illness. On the other hand, we suggest the upregulation of autophagy regulator MAP1LC3C and genes in the immune complement system (C7, C8A, & C9) as markers for disease severity in mild illness. Coinfection analysis revealed intensification of Streptococcus pneumoniae and decreasing of Cutibacterium acnes relative abundance in symptomatic patients to asymptomatic patients. The transcriptomic analysis of this study provides several candidates of molecular markers of COVID-19 severity, as well as offering the possibility of bacterial coinfection in worsening the symptoms.